Epibatidine alkaloid chemistry:: 5.: Domino-Heck reactions of azabicyclic and tricyclic systems - Yolacan, Cigdem; Bagdatli, Emine; Ocal, Nuket; Kaufmann, Dieter E. (MDPI, 2006)
Palladium-catalyzed hydroarylations and additional domino reactions of azabicyclic and tricyclic norbornene derivatives were investigated and a series of new epibatidine analogues were synthesized.
Keywords: epibatidine; palladium; hydroarylation; domino reactions; Heck reactions; alkynes; heterocycles; DERIVATIVES; Biochemistry & Molecular Biology; Chemistry